Risk factors for situs defects and congenital heart disease in primary ciliary dyskinesia. Issue 2 (30th August 2018) - Best, Sunayna; Shoemark, Amelia; Rubbo, Bruna; Patel, Mitali P; Fassad, Mahmoud R; Dixon, Mellisa; Rogers, Andrew V; Hirst, Robert A; Rutman, Andrew; Ollosson, Sarah; Jackson, Claire L; Goggin, Patricia; et al.
Abstract : Primary ciliary dyskinesia (PCD) is associated with abnormal organ positioning (situs) and congenital heart disease (CHD). This study investigated genotype–phenotype associations in PCD to facilitate risk predictions for cardiac and laterality defects. This retrospective cohort study of 389 UK patients with PCD found 51% had abnormal situs and 25% had CHD and/or laterality defects other than situs inversus totalis. Patients with biallelic mutations in a subset of nine PCD genes had normal situs. Patients with consanguineous parents had higher odds of situs abnormalities than patients with non-consanguineous parents. Patients with abnormal situs had higher odds of CHD and/or laterality defects.